BIOCOMPOSITE MODIFIED BITUMEN (BMB) FOR DURABLE PAVEMENT - AL-SABAEEI, ABDULNASER MOHAMMED (2021)
In recent years, there has been potential concern about the sustainability of infrastructure and environmental issues and the depletion of non-renewable resources for flexible pavement construction.